(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores modern requirements for developing the professional competence of future music teachers. It analyzes the essence of the concept of competence, the structural components of professional competence, as well as the knowledge, skills, and values essential for the professional activity of a music teacher. The study highlights the factors that contribute to improving teachers’ professional training based on modern educational standards and innovative pedagogical approaches.